EFFECT OF FEEDING TREATMENT WITH SOME EXTRACTS OF BLACK PEPPER ON SOME BIOLOGICAL ASPECTS OF COTTON LEAF WORM - & et al., AL-Khazraji (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This research was conducted to study the effect of food treatment leaves of Malva sylvestris with ethanol ,ethyl acetate, hexane and oil extract of black pepper fruits Piper nigrum on some biological aspects of cotton leaf worm Spodoptera littoralis by using the concentrations of 1.25, 2.5 and 5% of each extract, The results of feeding treatments of second larvae instar showed an increase in mortality percentages which reached 100% at the all extracts when using 5% concentrate. used in the test, while the highest mortality reached to 26.7% when using ethanol extract at 5% concentrate for sixth larvae instar fed on treated leaves for 24 hrs., it was also found that the period of larvae growth and pupae were prolonged by ethanol extract which reached to 33 days at the conc. 2.5% for the second larvae instar while reached 25 days in control, and pupae growth reached to 14 days at the same conc. while reached 10.3 days in control.